Teachers’ perceptions on empowerment / Aida Noor Izam Bujang - Bujang, Aida Noor Izam (2012)
Education reform is taking place in almost every country and Malaysia is not excluded from this. Education reform has brought to the concept of empowerment to the school staff. The purpose of this study was to determine the perceived degree of teacher empowerment in public schools and to identify the obstacles and facilitators to their teacher empowerment. The data were collected through a questionnaire returned by a sample of 69 public teachers using the School Participant Empowerment Scale (SPES), adopted from Short & Rinehart (1992). Teacher rated their overall empowerment 3.88 on a 5-point Likert-type scale (1 = strongly disagree, 5 = strongly agree). Dimensional ratings were : Professional Growth (4.18). Self-efficacy (4.16), Status (4.07), Impact (3.84), Autonomy (3.82) and Decision Making (3.48). The identified facilitating factors to empowerment most evident were opportunity to continue learning and respect. The identified limitation factor to empowerment most evident was the lack of opportunity in making decision. Future research could focus exploring the relationship between teacher empowerment and principal use of power. The possible extensions of this study could also explore the relationship between teachers' sense of empowerment and organisational commitment.